ADSORPTION OF Cu(II) ON ZEOLITE A SYNTHESIZED FROM COAL BOTTOM ASH OF PT. IPMOMI PAITON - Nurul Faradilah Said; Nurul Widiastuti (Jurnal Zeolit Indonesia, 2008)
The study aimed to utilizing coal bottom-ash into zeolite A that was used as absorber metal ion of Cu(II). Zeolite A is made from bottom-ash using alkali fusion followed by hydrothermal processes. Melting temperature of Alkali conducted at 750°C during 12 h ours and hydrothermal processes at 100°C with molar ratio of SiO2/Al2O3 1,9. The result XRD showed that zeolite was formed is zeolite A. Product of Zeolite A was examined the ability of adsorption metal ions of Cu (II). In this test conducted several parameter variations that influences are period, concentration, pH, and temperature. The result showed that zeolite A can adsorbing Cu(II) up to 83,35% with the concentration of Cu(II) 50mg/l at pH 8 for 360 minutes. This study was learning some aspects of adsorption process were kinetic adsorption and isothermal adsorption. The result indicate that the kinetics adsorption of Cu(II) at zeolit A was following model of pseudo-first order, while isothermal adsorption is following model of Freundlich.